Application of silvicultural system, yield regulation and thinning practices in natural forests: case study from western Terai - Subedi, V. R.; Bhatta, K. D.; Poudel, I. P.; Bhattarai, P. (Banko Janakari, 2018)
Harvesting of mature forest crop, regenerating the harvested area and tending of young crop are major silvicultural operations in forest management. Silvicultural system provides a framework for carrying out these silvicultural operations in a systematic manner. Yield is the annual amount of produce that can be realized sustainably. Similarly, thinning is the principal tending operation carried out in immature crop, is more often complicated in natural forest. This paper attempts to review silvicultural system applied in Terai region of Nepal under scientific forest management in order to regulate yield and to suggest new methods of thinning in natural forests. The study was conducted in Buddha Shanti Collaborative Forest in Nawalparasi district, western Terai Nepal. Data related to implementation status of CFM Plan were collected through field observation. Harvesting data were collected during harvesting operation. The collected harvesting data were analyzed for yield regulation. Irregular shelter-wood system was applied in Buddha Shanti CFM. The applied method of yield regulation is combination of area and stem control. Area control is applied for regeneration period. Annual harvest is controlled by number of stems. Tree harvesting area is fixed for ten years and annual harvesting amount is fixed by number of tree. In this method annual numbers of trees for harvesting are fixed. Total enumeration method was applied for thinning to find out the most frequent size of pole in selected sub compartment. During the enumeration process; distance between the every stem and fore bearing was also recorded with the help of laser distance meter and compass. A stem map was prepared with the help of Arc-GIS and the grid distance was fixed based on the most frequent size of stem. Then, one stem from each grid was selected for retaining after harvesting and remaining stems were cut down. This method provides appropriate guideline for implementing it objectively by reducing subjective judgment and provide more systematic method for thinning. The field practices of application of silvicultural system and yield regulation were found in accordance to the scientific forest management Procedures 2014 in Buddha Shanti CFM. The method for thinning applied in the CFM was found applicable to other similar type of forests. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page: 92-97